INVITRO ANTIBACTERIAL ACTIVITY OF ENDOPHYTIC FUNGAL EXTRACTS ISOLATED FROM A PHARMACEUTICALLY IMPORTANT PLANT FICUS RELIGIOSA L. - KALYANARAMAN RAJAGOPAL,; MAHESWARI SUNDHARAMOORTHY,; ARUMUGAM P.,; JASMITH BASHA W.,; KATHIRAVAN GOVINDARAJAN,; RADHAI RAJENDRAN, (International Journal of Pharma and Bio Sciences, 2015)
Ficus religiosa L is one of the important medicinal plant widely used in pharmaceutical research. It is widely distributed in India and a religiously important host. In the present study, antibacterial activity of endophytic fungi isolated from Ficus religiosa was carried out. Organic extract of five dominant endophytic fungi viz Botryodiplodia theobromae, Colletotrichum gloeosporioides, Phomopsis sp, Curvuleria lunata, Drechslera hawaiiensis were tested against important gram positive and gram negative bacteria. The C.lunata extract showed maximum activity against tested organisms followed by Colletotrichum gloeosporioides. However, Botryodiplodia theobromae does not inhibit any of the test organisms.